Paciente de sexo masculino de 85 años con Bronquitis Aguda - Alcívar Baquerizo, Ange Mirel (2020)
Most people with acute bronchitis recover after a few days or weeks. Viral infections, such as a cold or the flu, are usually the cause of acute bronchitis. Occasionally, acute bronchitis can be caused by a bacterial infection. Chronic bronchitis is a continuous cough that lasts several months and reoccurs for two or more consecutive years. In chronic bronchitis, the lining of the airways remains constantly inflamed. This causes the coating to swell and produce more mucus, which can make breathing difficult. Chronic bronchitis is often part of a serious condition called chronic obstructive pulmonary disease (COPD). The most common symptom of bronchitis is the cough associated with mucus production. Other symptoms include wheezing sound, shortness of breath, chest pain or low fever. To diagnose bronchitis, your doctor will do a physical exam, and ask about your medical history and symptoms. The doctor may also request a blood test to detect signs of infection or a chest x-ray to see if the lungs and bronchial tubes look normal and rule out pneumonia.